Efektifitas Perda Nomor 5 Tahun 2021 Tentang Pengelolaan Sampah Rumah Tangga dan Sampah Sejenis Sampah Rumah Tangga Di Kota Tabanan - Ida Ayu Made Ariskayanti; I Ketut Kasta Arya Wijaya; Luh Putu Suryani (Warmadewa Press, 2024)
The problem of waste is a problem that never ends from year to year. The volume of waste always increases every year and causes various negative impacts on the environment and the sustainability of people's lives. The population is affected by the increase in waste volume. With this background, the problem formulation raised is how the implementation of Tabanan Regency Regional Regulation Number 5 of 2021 concerning Waste Management in Tabanan City, and how the effectiveness of Tabanan Regency Regional Regulation Number 5 of 2021 in Tabanan City. This research uses empirical legal research type, data collection techniques in this research are by conducting interviews and document studies. The results of the study found that Tabanan Regency Regional Regulation Number 5 of 2021 concerning Management of Household Waste and Waste Similar to Household Waste has been implemented quite well but has not been fully effective because there are still several obstacles in the implementation of the regulation, namely low awareness and knowledge of waste management and lack of facilities and infrastructure in managing waste. Sanctions against waste violators are subject to administrative sanctions in the form of verbal and / or written warnings, as well as fines.